Arenaria goekyigitii (Caryophyllaceae), a new species from Turkey - Di̇nç Muhi̇tti̇n; Doğu, Süleyman (Phytotaxa, 2020)
Arenaria goekyigitii (Caryophyllaceae) is described as a new species from Karaman-Ermenek (Turkey). The new species is morphologically similar to A. angustifolia (=Arenaria yunus-emrei) from which mainly differs by the habit (mat-forming, slender vs. mat-forming, rigid in A. angustifolia), leaf shape (oblanceolate vs. linear-spathulate to linear in A. angustifolia), and seed surface (rugose-granulatelae vs. areolate-papillate in A. angustifolia). A detailed description, ecological data, original photos, and conservation status of the new species are given.